THE ROLE OF THE STATE IN THE IMPLEMENTATION OF DEMOCRACY AND HUMAN RIGHTS IN INDONESIA - Muh. Alfian (Yustisia, 2017)
This research aimed to examine to what extent the role of the State participation in applying the principles of democracy and human right in Indonesia. This research is normative legal research (library research). There are two obligations of state toward human rights namely, protection and realization. Protection requires  the role’s state to  guarantee and to protect human rights. Meanwhile, realization is obligation demanded  State to act actively  in keeping human rights.  Human Right violations aren’t only done by State, but also non-State actors covering either individual or corporation. The obligation and responsibility to keep  human rights are important because we are not only face human crimes, genocide or war crimes but also poverty and undeveloped. The obligation and reponsibility of corporation are realized in the form of   Corporate Social Responsibility , especially in community development.